2001
DOI: 10.1051/0004-6361:20011261
|View full text |Cite
|
Sign up to set email alerts
|

Envelope tomography of long-period variable stars

Abstract: Abstract. This paper presents statistics of the line-doubling phenomenon in a sample of 81 long-period variable (LPV) stars of various periods, spectral types and brightness ranges. The set of observations consists of 315 highresolution optical spectra collected with the spectrograph ELODIE at the Haute-Provence Observatory, during 27 observing nights at one-month intervals and spanning two years. When correlated with a mask mimicking a K0III spectrum, 54% of the sample stars clearly showed a double-peaked cro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 55 publications
(50 reference statements)
3
74
0
Order By: Relevance
“…Observational support to an inner atmospheric origin of the shocks comes from the velocity and temperature structures derived from the vibration-rotation CO ∆υ = 3 emission lines, which are consistent with the development of shock waves originating deeper than the line forming layers (Hinkle, Scharlach, & Hall 1984). Likewise, studies based on envelope tomography of long period variables suggest that the double absorption lines in their optical spectra are caused by the propagation of a shock wave through the photosphere (Alvarez et al 2001). …”
Section: The Shock Formation Radiusmentioning
confidence: 60%
“…Observational support to an inner atmospheric origin of the shocks comes from the velocity and temperature structures derived from the vibration-rotation CO ∆υ = 3 emission lines, which are consistent with the development of shock waves originating deeper than the line forming layers (Hinkle, Scharlach, & Hall 1984). Likewise, studies based on envelope tomography of long period variables suggest that the double absorption lines in their optical spectra are caused by the propagation of a shock wave through the photosphere (Alvarez et al 2001). …”
Section: The Shock Formation Radiusmentioning
confidence: 60%
“…This finding, along with the previous result for the minimum period allowed by the Roche radius, definitely denies the reality of the binary nature of HD 110 813. Alvarez et al (2001) have shown that S UMa exhibits an asymmetric cross-correlation dip, as usual among Mira variables. Asymmetric profiles observed in Mira variables are often associated with radial-velocity variations, which indeed mimick an orbital motion (see also Hinkle et al 2002).…”
Section: Fig 12mentioning
confidence: 61%
“…Both classes of variables often exhibit pseudo-orbital variations caused by shock waves associated with the envelope pulsation (Udry et al 1998;Hatzes & Cochran 1998;Wood 2000;Hinkle et al 2002;Setiawan et al 2004;Derekas et al 2006;Soszyński 2007;Hekker et al 2008). For semi-regular variables, Hinkle et al (2002) obtain semi-amplitudes K between 1.6 and 3.1 km s −1 , whereas for Miras the semi-amplitudes may reach 20 km s −1 in the most extreme cases (Alvarez et al 2001). In terms of standard deviations, these values become 1.1, 1.7, and 14 km s −1 , respectively (remember that for sinusoidal variations, σ = K/ √ 2).…”
Section: Photometric Variabilitymentioning
confidence: 99%
“…9.4 in Jorissen 2003a). Secondly, since they are LPVs, shock waves move across their atmospheres, and induce radial-velocity variations with amplitudes of 10 to 20 km s −1 (Hinkle et al 1997;Alvarez et al 2001). …”
Section: Relation With S and Barium Starsmentioning
confidence: 99%